2020
DOI: 10.1038/s41541-020-0157-x
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral vaccination protects against transcervical infection with Chlamydia trachomatis and generate tissue-resident T cells post-challenge

Abstract: The optimal protective immunity against Chlamydia trachomatis (C.t.) is still not fully resolved. One of the unresolved issues concerns the importance of resident immunity, since a recent study showed that optimal protection against a transcervical (TC) infection required genital tissue-resident memory T cells. An important question in the Chlamydia field is therefore if a parenteral vaccine strategy, inducing only circulating immunity primed at a nonmucosal site, should be pursued by Chlamydia vaccine develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 51 publications
3
33
0
Order By: Relevance
“…Additionally, Th1 CD4 + T cells may also produce IL-2 [ 35 , 48 ], IL-10 [ 49 , 50 ], TNF-α [ 51 ] and lymphotoxin [ 35 ]. Th1 cells can be found circulating within the periphery, and there is mounting evidence that Th1 CD4 + T cells can also express tissue resident phenotypes [ 52 , 53 ] and be found in tissues. IL-2 is known to be important in the generation of resident memory Th1 CD4 + T cells in the lungs of mice [ 52 ], and protective tissue resident CD69 + CD4 + Th1 cells can be generated by perinatal vaccination and found resident in the genital tract in humans [ 53 ].…”
Section: T Helper 1 Cells (Th1)mentioning
confidence: 99%
“…Additionally, Th1 CD4 + T cells may also produce IL-2 [ 35 , 48 ], IL-10 [ 49 , 50 ], TNF-α [ 51 ] and lymphotoxin [ 35 ]. Th1 cells can be found circulating within the periphery, and there is mounting evidence that Th1 CD4 + T cells can also express tissue resident phenotypes [ 52 , 53 ] and be found in tissues. IL-2 is known to be important in the generation of resident memory Th1 CD4 + T cells in the lungs of mice [ 52 ], and protective tissue resident CD69 + CD4 + Th1 cells can be generated by perinatal vaccination and found resident in the genital tract in humans [ 53 ].…”
Section: T Helper 1 Cells (Th1)mentioning
confidence: 99%
“…Nevertheless, our study results demonstrate that parenteral immunization of mice, at least with a wP vaccine, elicited an effective distant mucosal response with generation of lung T RM T cells. Recent studies, consistent with our findings, demonstrated similar effective mucosal memory response following s.c. parenteral vaccination in the genital tract and nasal tissue (54,55). Furthermore, in this outbred mouse model of memory immunity, we observed that vaccination by the i.m.…”
Section: Discussionmentioning
confidence: 63%
“…These cells have also been shown to correlate with protection [ 49 ]; moreover, they are essential for pathogen clearance [ 7 , 50 , 51 ]. During chlamydia infection in mice, naïve T cells differentiate into effector T cells in uterus-trafficking lymph nodes and these effector cells are then recruited to the mucosa of the genital tract to establish tissue-resident memory cells (T RM ) [ 21 , 52 , 53 ]. Furthermore, in 2015, Stary et al showed that the generation of “two waves of protective memory T cells,” tissue-resident CD4 T RM and circulating T CM and T EM cells, is required for optimal clearance of genital Ct infections [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This collaboration studied not only basic characteristics of the pig model relevant for translational Ct research, they also used their combined expertise for Ct vaccine development and demonstrated Ct vaccine efficacy and immunogenicity in naïve minipigs [ 10 ]. In their latest studies, the authors showed that protection against Ct genital infection in minipigs immunized with Ct vaccine formulated with CAF01 adjuvant was associated with cervical infiltration of CD4 + T cells [ 20 ] and tissue-resident memory CD4 + T cell infiltration into the uterus [ 21 ]. Käser et al provided a detailed view of the porcine T-cell immune response to Cs and Ct .…”
Section: Introductionmentioning
confidence: 99%